Structural analysis of the SARS-CoV-2 methyltransferase complex involved in RNA cap creation bound to sinefungin - Krafcikova, Petra; Silhan, Jan; Nencka, Radim; Boura, Evzen (Nature communications, 2020)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the cause of the COVID-19 pandemic. 2'-O-RNA methyltransferase (MTase) is one of the enzymes of this virus that is a potential target for antiviral therapy as it is crucial for RNA cap formation; an essential process for viral RNA stability. This MTase function is associated with the nsp16 protein, which requires a cofactor, nsp10, for its proper activity. Here we show the crystal structure of the nsp10-nsp16 complex bound to the pan-MTase inhibitor sinefungin in the active site. Our structural comparisons reveal low conservation of the MTase catalytic site between Zika and SARS-CoV-2 viruses, but high conservation of the MTase active site between SARS-CoV-2 and SARS-CoV viruses; these data suggest that the preparation of MTase inhibitors targeting several coronaviruses - but not flaviviruses - should be feasible. Together, our data add to important information for structure-based drug discovery.
Keywords: Coronavirus Infections; Adenosine; SARS-CoV-2; methyltransferasy; Viral Regulatory and Accessory Proteins; stabilita RNA; RNA Caps; RNA, Viral; adenosin; virové nestrukturální proteiny; Enzyme Inhibitors; Viral Nonstructural Proteins; lidé; koronavirové infekce; COVID-19; Methyltransferases; krystalografie rentgenová; Pneumonia, Viral; Betacoronavirus; virová pneumonie; pandemie; RNA virová; chemické modely; Models, Molecular; molekulární modely; katalytická doména; inhibitory enzymů; RNA Stability; virové regulační a přídatné proteiny; Models, Chemical; RNA čepičky; Crystallography, X-Ray; Pandemics; Catalytic Domain; Humans